Recent progress in nucleic acids isotachophoresis. Issue 1 (30th October 2017) - Datinská, Vladimíra; Voráčová, Ivona; Schlecht, Ulrich; Berka, Jan; Foret, František
Abstract: Progress achieved between 2014–2017 in the extraction and sample preparation of nucleic acid by isotachophoresis is reviewed in this paper. The isolation and purification of nucleic acids is very often compromised by a complex matrix such as blood and other bodily fluids, samples from the scene of crime, fossil samples, etc. While most of the common nucleic acids isolation techniques are based on extraction with inherent limitations with regard to quantitative results, isotachophoretic focusing is a quantitative process with a theoretically unlimited concentration factor. Since isotachophoresis belongs to less traditional approaches of nucleic acids purification, we present not only the latest developments in the application of isotachophoresis for the nucleic acids concentration but also a brief description of the principles of this method.